Novel Gold and Silver Carbene Complexes Exert Antitumor Effects Triggering the Reactive Oxygen Species Dependent Intrinsic Apoptotic Pathway. (6th December 2017) - Iacopetta, Domenico; Mariconda, Annaluisa; Saturnino, Carmela; Caruso, Anna; Palma, Giuseppe; Ceramella, Jessica; Muià, Noemi; Perri, Mariarita; Sinicropi, Maria Stefania; Caroleo, Maria Cristina; Longo, Pasquale
Abstract: Cisplatin and other platinum‐based drugs are well‐known valid anticancer drugs. However, during chemotherapy, the presence of numerous side effects and the onset of frequent phenomena of resistance has pushed many research groups to devise new metal‐based compounds holding improved anticancer properties and fewer undesired effects. Amongst the variety of synthesized compounds, significant antiproliferative effects have been obtained by employing organometallic compounds, particularly those based on silver and gold. With this in mind, we synthesized four compounds, two silver complexes and two gold complexes, with good inhibitory effects on the in vitro proliferation of breast and ovarian cancer‐cell models. The antitumor activity of the most active compound, that is, AuL4, was found to be ninefold higher than that of cisplatin, and this compound induced dramatic morphological changes in HeLa cells. AuL4 induced PARP‐1 cleavage, caspases 3/7 and 9 activation, mitochondria disruption, cytochrome c release in cancer‐cell cytoplasm, and the intracellular production of reactive oxygen species. Thus, AuL4 treatment caused cancer‐cell death by the intrinsic apoptotic pathway, whereas no cytotoxic effects were recorded upon treating non‐tumor cell lines. The reported outcomes may be an important contribution to the expanding knowledge of medicinal bio‐organometallic chemistry and enlarge the available anticancer toolbox, offering improved features, such as higher activity and/or selectivity, and opening the way to new discoveries and applications. Abstract : Silver & gold : All the compounds synthesized in this study are light‐ and water‐stable and possess antitumor properties, mostly against HeLa cells. AuL4 induces mitochondria disruption and cytochrome c release, which activates the intrinsic apoptotic pathway in a reactive oxygen species (ROS)‐dependent fashion.